Cathching Fire - Collins, Suzanne (New York Scholastic Press, 2009)
By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion. Tags from this library
Keywords: Young Adult Fiction -- Adventure -- Action Fiction